ANALYSIS ON SYMBOLISM OF MALANG MASK DANCE IN JAVANESE CULTURE - Dwi Malinda (JURNAL ILMIAH BAHASA DAN SASTRA, 2014)
ABSTRACT Malang Mask dance is an example of traditions in Java specially in Malang. It is interesting even to participate. This study has two significances for readers and students of language and literature faculty. Theoretically, the result of the study will give description about the meaning of symbols used in Malang Mask dance and useful information about cultural understanding, especially in Javanese culture.